Carotenoid accumulations and carotenogenic gene expressions in the petals of Eustoma grandiflorum. Issue 4 (14th May 2013) - Liu, Hui; Kishimoto, Sanae; Yamamizo, Chihiro; Fukuta, Naoko; Ohmiya, Akemi
Abstract: Eustoma grandiflorum is one of the leading cut‐flowers in Japan. There are market demands for cultivars with deep‐yellow flowers, but they have never been bred successfully. By investigating the carotenoid accumulation and carotenogenic gene expressions, this study attempted to explore the reasons that block the formation of deep‐yellow colour in Eustoma. High performance liquid chromatography analysis showed that the carotenoid compositions in petals were similar to those in leaves, accumulating mainly lutein, violaxanthin and β‐carotene. The total carotenoid contents decreased as the petals matured in all the cultivars tested. Quantitative real‐time PCR analysis showed that the expression levels of PSY, LCYB, ZDS and LCYE showed significant differences between white and pale‐yellow petals or between petals and leaves, indicating that these enzymes may play a key role in the carotenoid biosynthesis in E. grandiflorum . The expression levels of CCD4 were high in both pale‐yellow and white petals during development, suggesting that carotenoid degradation activity is high in the petals. We then conclude that the total carotenoid accumulation level could be determined by the balance between carotenoid biosynthesis and degradation activities.